The Integration of Character Values in the Equivalency Education Program at Ash-Shodiq Community Learning Center Lembang - Irnawati, Hanifah; Anshori, Anshori; Widiastuti, Novi (PEDAGOGIA, 2024)
The equal education program is designed to expand access to educational services for the community in order to improve the quality of human resources with character. PKBM Ash-Shoddiq as a provider of equal education that grows from, by and for the community contributes to producing graduates with character. The aim of this research is to describe data regarding the application of character values in the equality education program at PKBM Ash-Shoddiq. The theoretical study used is the concept of character education and equality education programs. The research approach used is a qualitative approach with a case method. Data collection techniques were carried out through interviews, literature study, documentation and observation. The research subjects were managers, tutors, learning residents and the foundation's board of trustees. The research results show that the application of character values in the equality education program is carried out in an integrated and holistic manner that combines character values and life skills education. The character values that are built are politeness, healthy lifestyle, independence, usefulness, having work and filial piety, where in the holistic-integration approach, the tutor's competence in developing the character and life skills of students is not separated from their competence in teaching academic subjects. On the contrary, both are considered an integral part of the tutor's responsibility in forming individuals with integrity and potential. The researcher concluded that this approach recognizes the importance of developing the character of students in a balanced manner with the mastery of academic knowledge and life skills.